Manajemen Perubahan dan Pengelolaan SDM Digital dalam Membangun Budaya dan Etika Organisasi Perusahaan (studi kasus di PT Niaga Bunga Creative) - Muammar Afif Al Qusaeri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the implementation of change management and digital human resource management and their role in building organizational culture and ethics at PT Niaga Bunga Creative. This study uses a qualitative approach with a case study to gain a deeper understanding of the change management and digital human resource management processes in building organizational culture and ethics at PT Niaga Bunga Creative. Data collection was conducted through in-depth interviews, direct observation, and documentation to obtain a comprehensive picture of change practices, HR behaviors, and evolving work values ​​within the organization. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data presentation, and continuous drawing and verification of conclusions. The results indicate that organizational changes at PT Niaga Bunga Creative improved the company's readiness to face digital-based work demands through shifts in work systems and human resource management. These changes encouraged the creation of more flexible and efficient work patterns and increased employee adaptability and competence in the digital work environment. Furthermore, the change process strengthened a collaborative and responsible work culture and fostered a work ethic reflected in discipline, professionalism, and quality work communication.